Enhancing rice panicle branching and grain yield through tissue-specific brassinosteroid inhibition - Zhang, X.; Meng, W.; Liu, D.; Pan, D.; Yang, Y.; Chen, Z.; Tong, H.
Crop yield potential is constrained by the inherent trade-offs among traits such as between grain size and number. Brassinosteroids (BRs)promote grain size, yet their role in regulating grain number is unclear. By deciphering the clustered-spikelet rice germplasm, we show that activation of the BR catabolic gene BRASSINOSTEROID-DEFICIENT DWARF3 (BRD3)markedly increases grain number. We establish a molecular pathway in which the BR signaling inhibitor GSK3/SHAGGY-LIKE KINASE2 phosphorylates and stabilizes OsMADS1 transcriptional factor, which targets TERMINAL FLOWER1-like gene RICE CENTRORADIALIS2. The tissue-specific activation of BRD3 in the secondary branch meristems enhances panicle branching, minimizing negative effects on grain size, and improves grain yield. Our study showcases the power of tissue-specific hormonal manipulation in dismantling the trade-offs among various traits and thus unleashing crop yield potential in rice.